2010
DOI: 10.12968/jowc.2010.19.11.79695
|View full text |Cite
|
Sign up to set email alerts
|

Predicting delayed pressure ulcer healing using thermography: a prospective cohort study

Abstract: Our results indicate that using thermography to classify pressure ulcers according to temperature could be a useful predictor of healing at 3 weeks, even though wound appearances may not differ at the point of thermographical assessment. The higher temperature in the wound site, when compared with periwound skin, may imply the presence of critical colonisation, or other factors which disturb the wound healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
84
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 8 publications
1
84
0
Order By: Relevance
“…A higher temperature in the peri-wound skin compared with that in the wound may indicate critical colonization. 16 This technique was applied for all patients. …”
Section: Training In Advanced Pu Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher temperature in the peri-wound skin compared with that in the wound may indicate critical colonization. 16 This technique was applied for all patients. …”
Section: Training In Advanced Pu Managementmentioning
confidence: 99%
“…15 Thermography has been tested to detect latent inflammation in PUs, including those with critical colonization. 16 Nakagami et al reported that PUs were classified into two groups depending on whether the wound site temperature was lower or higher than the peri-wound skin temperature; a higher wound site temperature may imply the presence of critical colonization. 16 However, international studies on the mechanisms and effects of critical colonization are only in the early stages, and no interventional studies have focused on DTI and critical colonization with the aim of preventing PU deterioration or providing systematic protocols for the management of PUs.…”
Section: Introductionmentioning
confidence: 99%
“…Wearable temperature sensors are important as the temperature of the human body is considered as one of the main vital signs that are measured and monitored in hospital patients [1], with temperature being a useful method to detect various pathologies, including infection in wounds [2][3][4]. This work builds on previous studies that have created a wearable temperature sensing yarns [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Although IR and LSCI techniques have been used previously to examine ulcerated tissue [8][9][10], low-frequency oscillations of temperature and blood flow related to vascular tone have yet to be assessed. We hypothesize that fluctuations in these parameters could be used as sensitive, non-invasive markers to quantify different aspects of vascular pathophysiology in the ulcer bed and surrounding tissues.…”
Section: Introductionmentioning
confidence: 99%